A convenient and efficient synthesis method to improve the emission intensity of rare earth ion doped phosphors: the synthesis and luminescent properties of novel SrO:Ce3+ phosphor. Issue 114 (3rd November 2015) - Fu, Jipeng; Zhang, Su; Ma, Tengfei; Jia, Yonglei; Pang, Ran; Jiang, Lihong; Li, Da; Li, Haifeng; Sun, Wenzhi; Li, Chengyu
Abstract : A convenient and efficient synthesis method that improves the emission intensity of rare earth ion doped phosphors is proposed. This approach can greatly improve the reaction temperature and overcome the requirement for harsh conditions. Abstract : Convenient, efficient synthesis methods that improve the emission intensity of rare earth ion doped phosphors are relatively rare. In this study, a simple modified solid-state reaction is proposed. This approach can greatly improve reaction temperature and overcome the requirement for harsh conditions. Its advantages come from the substitution of a solid–solid interface for a solid–gas interface. A novel Ce 3+ doped SrO phosphor with an enhancive bright cyan emission is prepared and the photoluminescent properties of SrO:Ce 3+ are first reported. This study will provide valuable clues for synthesizing many other ion doped functional materials besides rare earth ion doped luminescent materials.